Obstacles in the detection and reporting of tuberculosis cases: a discursive analysis - Fernando Mitano; Amélia Nunes Sicsú; Luciana de Oliveira Sousa; Rarianne Carvalho Peruhype; Jaqueline Garcia de Almeida Ballestero; Pedro Fredemir Palha
ABSTRACT Objective: To analyze the discourses of health professionals about the obstacles in the process of detection and reporting of tuberculosis cases in Mozambique. Method: Qualitative exploratory study with a theoretical-methodological approach of Discourse Analysis of French matrix. The study was conducted in Mozambique in 2014 at three levels: central, provincial and district. The study included 15 health professionals, 4 physicians, 6 technicians and 5 nursing professionals, who worked in the National Tuberculosis Control Program, with more than 1 year of experience. Result: The following discursive blocks emerged: Detection of tuberculosis cases in laboratories; Underreporting of tuberculosis cases; Obstacles to detect cases of tuberculosis: long distances and lack of transport; and Reporting of cases for decision making. Final considerations: The discourses analyzed point to the ideological affiliation that includes the lack of investment policies in the health sector and the political commitment as basic obstacles in the detection and reporting of tuberculosis cases.